2020
DOI: 10.1111/hir.12299
|View full text |Cite
|
Sign up to set email alerts
|

Health sciences libraries in Germany: new directions

Abstract: This feature is part of a series about medical library services in various countries. It gives an overview of the state of and selected current developments of medical library services to support research, education and clinical practice in Germany. Findings from an online survey and issues of access to health information are discussed in relation to the German health care system.J.M.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Germany (Knüttel et al, 2020) Our survey of new services provided by medical libraries found that most libraries assist with the development of search strategies. However full mediated searches for researchers working on systematic reviews, clinical guidelines and similar publications are less common.…”
Section: Overview and Questions To Considermentioning
confidence: 99%
See 2 more Smart Citations
“…Germany (Knüttel et al, 2020) Our survey of new services provided by medical libraries found that most libraries assist with the development of search strategies. However full mediated searches for researchers working on systematic reviews, clinical guidelines and similar publications are less common.…”
Section: Overview and Questions To Considermentioning
confidence: 99%
“…Germany (Knüttel et al, 2020) Laws and regulations governing the German medical curricula are currently being revised in order to adapt the structure and content of the curricula to meet current requirements imposed on the medical profession. There is a greater emphasis on teaching basic science skills with a specific focus on evidence-based medicine.…”
Section: Overview and Questions To Considermentioning
confidence: 99%
See 1 more Smart Citation
“…Canada (Ganshorn & Giustini, 2017) In Canadian health care facilities, librarians are increasingly taking on more roles that involve embeddedness in teams or other forms of research support. Germany (Knüttel et al, 2020) In recent years, university libraries in Germany have built up research data management services…. (p. 86) Usually, libraries collaborate with university computing centres and central research departments and form collaborative networks on a regional level.…”
Section: Supporting Researchers Engaging In Research Data Management (Rdm) and Maintaining Institutional Repositoriesmentioning
confidence: 99%
“…our focus must be to ensure that NHS-funded content is discoverable via as many routes as possible. (p. 72).Germany(Knüttel et al, 2020) Non-traditional library services provided by many health sciences libraries are experiencing increasing take-up.(p. 87) These services include teaching and focus on research support….…”
mentioning
confidence: 99%